2001
DOI: 10.1053/jhep.2001.21999
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisomal Proliferator Clofibrate Enhances the Hepatic Cytoplasmic Movement of Fatty Acids in Rats

Abstract: The role of cytosolic fatty acid binding protein (FABP) in cellular fatty acid metabolism remains poorly defined. The intracellular movement of fatty acids is thought to be facilitated through codiffusion with FABP. Peroxisomal proliferators like clofibrate induce FABP and may stimulate fatty acid use by increasing cytoplasmic diffusion rates. Our aim was to determine if induction of FABP by clofibrate increases the cytoplasmic transport of a fluorescent fatty acid NBD-stearate. Male rats were fed clofibrate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…5). Although we did not directly evaluate PPAR␣-regulated gene expression in the clofibratetreated rats, it is reasonable to assume in light of our previous and other studies (Bass et al, 1989;Kaikaus et al, 1993a;Luxon et al, 2000;Milliano and Luxon, 2001) that clofibrate treatment restored the parameters such as L-FABP and FACO that are down-regulated by ethanol.…”
Section: Ppar␣ and Alcoholic Livermentioning
confidence: 85%
See 1 more Smart Citation
“…5). Although we did not directly evaluate PPAR␣-regulated gene expression in the clofibratetreated rats, it is reasonable to assume in light of our previous and other studies (Bass et al, 1989;Kaikaus et al, 1993a;Luxon et al, 2000;Milliano and Luxon, 2001) that clofibrate treatment restored the parameters such as L-FABP and FACO that are down-regulated by ethanol.…”
Section: Ppar␣ and Alcoholic Livermentioning
confidence: 85%
“…Based on the observation in the present study that decreased levels of PPAR␣-responsive genes contribute or are at least permissive to alcoholic liver injury, it was of interest to determine whether administration of clofibrate, a potent activator of PPAR␣, would ameliorate the adverse effects of alcohol on the liver. Clofibrate, in addition to being a PPAR␣ ligand, also stimulates the transport of fatty acids in hepatocytes (Milliano and Luxon, 2001) and increases levels of L-FABP (Kaikaus et al, 1993c). Clofibrate administration to ethanol-fed rats led to a marked decrease in the degree of fatty liver (Table 2; Fig.…”
Section: Ppar␣ and Alcoholic Livermentioning
confidence: 99%
“…With MPFPR, it was shown for the first time that L-FABP gene ablation specifically reduced by 2-fold the cytoplasmic, but not membrane, component of fatty acid transport/diffusion in cultured primary hepatocytes. Although earlier studies of NBDstearic acid diffusion in transfected cells, hepatocytes from drug-treated animals, and hepatocytes of male versus female mice suggested that L-FABP influenced the intracellular diffusion of NBD-stearic acid (1,42,43,45), these studies utilized confocal FPR to obtain an average diffusion coefficient of NBDstearic acid (i.e. membranes ϩ cytoplasm) and did not resolve the cytoplasmic from the membrane components of NBD-stearic acid diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Stearic Acid-The effective diffusion coefficient (D eff ) of NBD-stearic acid is an established method for determining intracellular fatty acid transport/diffusion (1,(42)(43)(44)(45). To determine whether L-FABP gene ablation altered the intracellular transport/diffusion of fatty acid, the effective diffusion coefficient (D eff ) of NBD-stearic acid was determined in cultured hepatocytes by MPFPR.…”
Section: Determination Of Intracellular Fatty Acid Transport/diffusiomentioning
confidence: 99%
“…More than 20 years ago, Tipping and Ketterer (32) proposed that soluble binding proteins may stim-ulate cytoplasmic transport of their ligands by increasing their aqueous solubility. FABP has been shown to stimulate intracellular fatty acid mobility in cultured cells (18,20,22,23), perfused rat liver (16,19), and artificial cytoplasm (29,38), whereas knock out of the gene for heart FABP was found to greatly impair cardiac fatty acid metabolism (3). Weisiger and co-workers (15,16,20) have shown that the rate of fatty acid diffusion within liver cells is directly proportional to the concentration of liver FABP, and they have proposed that soluble binding proteins act as an aqueous carrier system that reduces binding of fatty acids and other molecules to immobile cytoplasmic membranes (20,37).…”
mentioning
confidence: 99%